Service enhancement in the hardware sector by Lean, MRP, and SLP tools - Martinez-Palacios, Asley; Barron-Vasquez, Hernan; Quiroz-Flores, Juan-Carlos (LACCEI, 2023)
In Peru, by 2020, SMEs will represent 95% of the companies and employ 26% of the EAP; however, it is known that SMEs have some problems that limit their sustainability. According to the literature, this results from situations such as being unable to maintain an adequate level of service, a non-existent organization in the warehouse, lack of knowledge of product locations, errors in picking, and uncertain availability and reliability of information in real-time, procurement is not based on any guidelines, stock breakage, and human error. Consequently, there is a low level of service in the companies. This problem has been evidenced in other investigations. For this reason, in the present investigation, a solution is proposed through the application of an improvement model using mixed tools implementing SLP, VRP, MRP 5S, and POKA YOKE to increase the current service level of 68% derived from the poor organization of the warehouse and processes, deficient manpower and poor inventory prevention. A model with 3 components is proposed: data collection, 5S implementation at all levels, route design, warehouse redesign, and demand forecasts to be validated and compared with their respective indicators.